2012
DOI: 10.1021/ct300042p
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Adsorption on Graphene: From Isolated Adatoms to Metallic Sheets

Abstract: We have studied Li adsorption on graphene for Li concentrations ranging from about 1% to 50% by means of density functional theory calculations. At low adsorbant densities, we observe a strong ionic interaction characterized by a substantial charge transfer from the adatoms to the substrate. In this low concentration regime, the electronic density around the Li adatoms is well localized and does not contribute to the electronic behavior in the vicinity of the Fermi level. For larger concentrations, we observe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 49 publications
8
55
1
Order By: Relevance
“…Important examples include atoms such as H, F, and O adsorbed on graphene to provide a suitable band gap for transistor applications. [3][4][5][6][7] Moreover, atoms adsorbed on 2D materials are potentially useful for ion batteries, 8 hydrogen storage materials, 9 and superconductors. 10 The physical and chemical properties of a material depend on its specific structure.…”
Section: Introductionmentioning
confidence: 99%
“…Important examples include atoms such as H, F, and O adsorbed on graphene to provide a suitable band gap for transistor applications. [3][4][5][6][7] Moreover, atoms adsorbed on 2D materials are potentially useful for ion batteries, 8 hydrogen storage materials, 9 and superconductors. 10 The physical and chemical properties of a material depend on its specific structure.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In particular, several theoretical studies show that Li ions are not likely to interact strongly with the basal plane of defect-free graphene and that chemisorption is only possible at defect sites. [18][19][20][21] Studies of lithium interaction and diffusion on graphene with topological defects such as Stone-Wales (SW), double vacancies (DV), and single vacancies (SV) 16,17,22 suggest attractive Li interaction with the vacancies, possibly enhancing Li adsorption. 16 Additionally, graphene functionalization with F, O, and H species have been of high interest.…”
Section: Introductionmentioning
confidence: 99%
“…Taken from Ref. 245 Simulation studies in the area can be largely divided into two sets, MD simulations of electrolytes at graphene (see Section 'Simulations of Electrolytes at Graphene Interfaces'), and DFT calculations investigating the adsorption of the Li + to the graphene electrodes [247][248][249][250][251][252][253][254][255][256][257][258][259] which are discussed below. The maximum Li capacity of graphite is 372 mA h/g, where Li + atoms are adsorbed as LiC 6 in a ( √ 3× √ 3)R30 • structure, with the Li + atoms located in the hollow sites.…”
Section: Lithium/alkali Metal Batteriesmentioning
confidence: 99%
“…244,246,247 Some initial theoretical studies predicted that a sheet of graphene was able to exceed the maximum theoretical capacity of graphite due to the adsorption of Li atoms to both surfaces of the sheet, allowing a higher Li/C ratio than 1:6. 246,250,252,254 In particular, it has been predicted that a Li 2 C 2 structure was theoretically stable, 250,251 with one Li ion adsorbing atop a carbon atom and another Li ion adsorbing above the C atom on the opposite side of the sheet, with the result of the graphene sheet buckling and forming a structure similar to that of graphane. However, more recent theoretical studies 247,260,261 (supported by Raman spectra that show that the intercalation of Li in few-layer graphene resembles that of graphite 262 ) have suggested that that pristine graphene systems may have a theoretical Li + capacity that is lower than that of graphite.…”
Section: Lithium/alkali Metal Batteriesmentioning
confidence: 99%